Effect of Climate Variability on Crop Yield in Nigeria (1980-2020) - Ideki, O.; Nwaerema, P.; Abali, T. P. (European Journal of Applied Sciences, 2024)
This study examined the effect of climate variability on crop yield from 1980-2020 in Nigeria. Rainfall and temperature data were obtained from the Community Climate System Model website. In contrast, the crop yield of five cereal crops namely cassava, maize, sweet potatoes, yam, and plantain were obtained from the African Center for Statistics of the United Nations Economic Commission for Africa (UNECA) Addis Ababa for the same period. The data sets were analyzed using descriptive and inferential statistics. The results of the analysis revealed that the mean values of rainfall and temperature are 1259.4237mm and 25oC respectively for the 41 years of the study. Furthermore, the regression analysis indicates an increasing trend for the two climate parameters. At the same time, cassava has the highest yield of 101,449.4390 hg/ha the highest followed by yam 920,75.2678hg/ha, plantain 622,92.3659 hg/ha, sweet potatoes 475,06.0488hg/ha and the crop with the least yield was maize 146,60.0488 hg/ha. However, the analysis of the effect of climate variability on crop yield revealed that sweet potatoes and maize correlated significantly with rainfall and temperature demonstrating the effect of climate variability on crop yield. This implies that both maize and sweet potatoes were the most sensitive to climate variability while cassava, plantain, and yam were the least sensitive crops. The study recommended mainstreaming the weather index crop insurance scheme into the Nigeria Agricultural Insurance Corporation (NAIC) to help and modulate the loss and production risk arising from extreme climate events. There is also a need to pay close attention to factors outside rainfall and temperature in explaining low and inconsistent yield in Nigeria. Also, farmers should take factors like soil fertility, untimely planting, improper selection of cropping systems, diseases, and pest infestation among others into consideration